2001
DOI: 10.1016/s0735-1097(01)01197-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of noninvasive markers in identifying patients at risk in the brugada syndrome: insight into risk stratification

Abstract: Late potentials are a noninvasive risk stratifier in patients with Brugada syndrome. These results may support the idea that conduction disturbance per se is arrhythmogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(84 citation statements)
references
References 26 publications
5
79
0
Order By: Relevance
“…Clinically, late potentials are consistently found in signalaveraged ECGs. 7,16 -20 They have a higher prevalence in Brugada syndrome patients, 17 are associated with malign (covedtype) ST elevations, 20 and are exacerbated by flecainide. 19 They and other markers of slow conduction are associated with stronger inducibility of ventricular tachyarrhythmias.…”
Section: Tukkie Et Al Activation Delay In Brugada Syndrome 1275mentioning
confidence: 99%
“…Clinically, late potentials are consistently found in signalaveraged ECGs. 7,16 -20 They have a higher prevalence in Brugada syndrome patients, 17 are associated with malign (covedtype) ST elevations, 20 and are exacerbated by flecainide. 19 They and other markers of slow conduction are associated with stronger inducibility of ventricular tachyarrhythmias.…”
Section: Tukkie Et Al Activation Delay In Brugada Syndrome 1275mentioning
confidence: 99%
“…8,[17][18][19] Depolarization abnormality is reflected in prolonged HV intervals, abnormal late potential and abnormal delayed potential in the epicardial region of the right ventricular outflow tract. 8,16,[20][21][22] A widening of the S wave in the right precordial leads, reflecting an underlying right ventricular conduction delay, was frequently observed in symptomatic patients and might be an important indicator of increased risk. 23 However, rate-dependent changes in the conduction abnormality have not been fully elucidated.…”
Section: Rate-dependent Changes In S Wave and Qrs Durationmentioning
confidence: 99%
“…[15][16][17] We previously reported that low-amplitude fragmented and delayed potentials were recorded in the RVOT in patients with Brugada syndrome and that these electrograms showed more fractionation and disorganization with programmed ventricular stimulation that led to VF. 14) In addition, several reports have shown a high incidence of ventricular late potentials, 18,19) high rate of induction of ventricular fibrillation (VF) by programmed ventricular stimulation, [20][21][22][23][24] and that inducibility of VF is increased more by programmed stimulation from the RVOT than from the RV apex in Brugada syndrome. 25,26) The aim of this study was to investigate the characteristics of the induced ventricular tachycardia (VT) that degenerates to VF to evaluate whether the RVOT is the arrhythmogenic focus in Brugada syndrome in a retrospective manner.…”
Section: Discussionmentioning
confidence: 99%